A bimetallic oxide lubricating composite coating and preparation method thereof

By forming a NiAl-MoO3/Bi2O3 composite coating on high-temperature structural parts, a lubricated glaze film is generated by the friction chemical reaction between MoO3 and Bi2O3, the problem of poor friction performance of traditional coatings at medium temperature is solved, and the problem of 400℃~800 The low friction coefficient and wear rate in the ℃ range meet the lubrication needs of high-temperature structural parts.

CN114015961BActive Publication Date: 2024-12-13SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111308766.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-05
Publication Date
2024-12-13
Estimated Expiration
2041-11-05

AI Technical Summary

Technical Problem

Traditional solid lubricants are oxidized and decomposed or volatile at above 400°C, resulting in poor frictional performance of the coating of high-temperature structural parts at medium temperatures, which is difficult to meet actual needs.

Method used

The composite coating is lubricated with bimetal oxide, including the substrate, transition layer and surface layer. The transition layer is a NiAl phase and the surface layer contains MoO3 and Bi2O3. It is formed by plasma spraying technology. MoO3 and Bi2O3 are easily generated by friction chemical reaction at high temperatures. Shear structure to form a lubricated glaze film and improve friction performance.

Benefits of technology

The friction coefficient and wear rate in the range of 400°C to 800°C are significantly reduced, forming a continuous lubricating layer, and improving the medium-temperature high-temperature tribological properties of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114015961B_ABST
    Figure CN114015961B_ABST
Patent Text Reader

Abstract

The present invention discloses a bimetallic oxide lubricating composite coating and a preparation method thereof, comprising a substrate, a transition layer covering the substrate and a surface layer covering the transition layer, wherein the transition layer is a NiAl phase, the surface layer comprises a NiAl transition phase and an oxide ceramic phase, and the oxide ceramic phase comprises MoO3 and Bi2O3. The present invention greatly improves the friction performance of the coating at medium temperature, avoids the problem of severe wear of the bimetallic oxide coating under medium temperature conditions, and can meet practical needs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal spraying materials and coatings, and in particular relates to a bimetallic oxide lubricating composite coating and a preparation method thereof. Background Art

[0002] With the continuous development of high-tech fields such as aviation and aerospace, the lubrication and wear reduction of materials in high-temperature structural parts are receiving more and more attention. Since the operating temperature of grease is below 400°C, high-temperature structural parts rely on solid lubricating coatings with good self-lubricating properties to increase the service life of the substrate; however, traditional solid lubricants (graphite, molybdenum disulfide and lead) are severely oxidized and decomposed or volatilized above 400°C. Therefore, it is urgent to develop new solid lubricants to improve the high-temperature self-lubricating properties of protective coatings.

[0003] Metal oxides have high melting points and excellent high-temperature chemical stability, so they are ideal lubricating phases for high-temperature solid lubricating coatings. The results show that metal oxides such as CuO / MoO3 are designed as the second phase of the protective coating. Binary metal oxides such as molybdates generated by tribochemical reactions have a shear-prone crystal microstructure induced by high-temperature friction heat-mechanical coupling, which can significantly improve the lubrication performance of the coating. The MoO3 / CuO composite coating deposited by plasma spraying shows a low friction coefficient and wear rate at a high temperature of 800℃, but this type of coating has poor friction performance at medium temperature (400-600℃), resulting in severe wear of the binary metal oxide coating under medium temperature conditions, which is difficult to meet actual needs. Summary of the invention

[0004] In response to the problems existing in the prior art, the present invention provides a bimetallic oxide lubricating composite coating and a preparation method thereof, which greatly improves the friction performance of the coating at medium temperature, avoids the problem of severe wear of the bimetallic oxide coating under medium temperature conditions, and can meet actual needs.

[0005] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:

[0006] A bimetallic oxide lubricating composite coating comprises a substrate, a transition layer covering the substrate and a surface layer covering the transition layer, wherein the transition layer is a NiAl phase, the surface layer comprises a NiAl transition phase and an oxide ceramic phase, and the oxide ceramic phase comprises MoO3 and Bi2O3.

[0007] Furthermore, in terms of mass percentage, in the surface layer, the NiAl transition phase accounts for 70wt% to 80wt%, and the oxide ceramic phase accounts for 20wt% to 30wt%.

[0008] Furthermore, the thickness of the transition layer is 40 μm to 50 μm, and the thickness of the surface layer is 180 μm to 200 μm.

[0009] Furthermore, the mass ratio of the MoO3 to the Bi2O3 is (1-2):1.

[0010] Furthermore, the substrate is a nickel-based high-temperature alloy.

[0011] A method for preparing a bimetallic oxide lubricating composite coating comprises:

[0012] Dissolving MoO3 and Bi2O3 in deionized water, mixing evenly, and drying to obtain a first composite powder;

[0013] The first composite powder and the NiAl powder are uniformly mixed to obtain a second composite powder;

[0014] On the substrate, the NiAl phase is sprayed by plasma spraying technology to form a transition layer;

[0015] The second composite powder is sprayed on the transition layer by plasma spraying technology to form a surface layer including a NiAl transition phase and an oxide ceramic phase, that is, a bimetallic oxide lubricating composite coating is obtained.

[0016] Furthermore, when MoO3 and Bi2O3 are dissolved in deionized water, in terms of mass percentage, the MoO3 and Bi2O3 account for 30% to 60%, and the deionized water accounts for 40% to 70%.

[0017] Furthermore, the drying temperature is 60-80°C.

[0018] Furthermore, when the first composite powder and NiAl powder are mixed, the first composite powder accounts for 20% to 30% and the NiAl powder accounts for 70% to 80% by mass.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects: a bimetallic oxide lubricating composite coating provided by the present invention comprises a substrate, a transition layer covering the substrate and a surface layer covering the transition layer, the transition layer is a NiAl phase, the transition layer provides a good bonding layer for the surface layer and the substrate, the surface layer is a NiAl phase and an oxide ceramic phase, the oxide ceramic phase comprises MoO3 and Bi2O3, the surface layer contains an oxide ceramic phase and a NiAl phase, which can be well adapted to the transition layer, improve the bonding force, and improve the high temperature resistance and wear resistance of the surface layer by MoO3 and Bi2O3, specifically, based on MoO3 (795°C) and Bi2O3 (825°C) powders with similar melting points as raw materials, it will soften at 0.4-0.7Tm (about 320-560°C), and form Bi2MoO6, Bi2Mo3O 12 The lubricating glaze film composed of NiMoO4 ternary metal oxides greatly improves the medium-temperature tribological properties of the coating. At the same time, the Ni content in the NiAl transition phase accounts for a large proportion, which can also greatly improve the high-temperature resistance of the transition phase.

[0020] In other words, the NiAl composite coating was prepared by plasma spraying with MoO3 and Bi2O3, which have similar melting points, as high-temperature lubricants. The composite coating showed excellent tribological properties. In particular, the friction coefficient and wear rate were significantly reduced in the range of 400℃ to 800℃. NiMoO4 and Bi2Mo3O 12 The synergistic lubrication effect of Bi2MoO6 forms a continuous lubrication layer on the surface, further improving the high-temperature tribological properties of the composite coating.

[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the specific implementation modes of the present invention, the drawings required for use in the description of the specific implementation modes will be briefly introduced below. Obviously, the drawings described below are some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 The cross-sectional morphology and element distribution of the composite coating of Example 2.

[0024] Figure 2 It is the friction coefficient of the composite coating of Example 2 at 27-800°C.

[0025] Figure 3 The wear rate of the composite coating of Example 2 at 27-800°C.

[0026] Figure 4 This is the Raman image of the wear scar surface of the composite coating in Example 2 at 400°C. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] As a specific embodiment of the present invention, a bimetallic oxide lubricating composite coating includes a substrate, a transition layer covering the substrate and a surface layer covering the transition layer, the thickness of the transition layer is 40μm to 50μm, and the thickness of the surface layer is 180μm to 200μm.

[0029] in:

[0030] The transition layer is NiAl phase;

[0031] In terms of mass percentage, the surface layer includes 70wt% to 80wt% of NiAl transition phase and 20wt% to 30wt% of oxide ceramic phase;

[0032] Oxide ceramic phases include MoO3 and Bi2O3;

[0033] The substrate is a nickel-based high-temperature alloy.

[0034] The present invention provides a method for preparing a bimetallic oxide lubricating composite coating, comprising the following steps:

[0035] Step 1, by mass percentage, dissolving 30% to 60% of MoO3 and Bi2O3 in 40% to 70% of deionized water, mixing them thoroughly by mechanical ball milling, and drying them at 60 to 80° C. to obtain a first composite powder;

[0036] Wherein, the mass ratio of MoO3 and Bi2O3 is (1-2):1;

[0037] Step 2, by mass percentage, 20% to 30% of the first composite powder and 70% to 80% of the NiAl powder are placed in a three-dimensional mixer and mixed for 5 to 10 hours to mix evenly, and then placed in a 60° C. to 90° C. oven to obtain a second composite powder;

[0038] Step 3: On the substrate, the NiAl phase is sprayed by plasma spraying technology, that is, the NiAl phase is deposited on the Inconel 718 high temperature alloy by plasma spraying technology. On top, a transition layer is formed;

[0039] Step 4: Spray the second composite powder onto the transition layer by plasma spraying technology to form a surface layer comprising a NiAl transition phase and an oxide ceramic phase, thereby obtaining a dense NiAl-MoO3 / Bi2O3 composite coating, i.e., a bimetallic oxide lubricating composite coating.

[0040] Example 1

[0041] Step 1: Dissolve 30% of MoO3 and Bi2O3 in 70% of deionized water by mass percentage, mix thoroughly by mechanical ball milling, and dry, wherein the mass ratio of MoO3 to Bi2O3 is 1:1, and the drying temperature is 60°C.

[0042] Step 2: According to the mass percentage, 20% of the first composite powder and 80% of the NiAl powder are placed in a three-dimensional mixer and mixed for 5 hours, and then placed in a 60° C. oven for drying to obtain a second composite powder.

[0043] Step 3: On the substrate, NiAl phase is deposited on Inconel718 high temperature alloy by plasma spraying technology. A transition layer is formed on the substrate, and the thickness of the transition layer is 40 μm.

[0044] Step 4: Spray the second composite powder onto the transition layer by plasma spraying technology to form a surface layer comprising a NiAl transition phase and an oxide ceramic phase. The thickness of the surface layer is 200 μm, thereby obtaining a bimetallic oxide lubricating composite coating.

[0045] The performance of the obtained bimetallic oxide lubricating composite coating was tested: the surface hardness of the coating was 167.8±18.2Hv0.5; the bonding strength was 45.7±4.9Mpa; the high temperature friction test (27-800℃, ball-disc contact, dual ball material zirconia, rotation radius 5mm, rotation speed 200r / min, load 10N): friction coefficient 0.22-0.45, wear rate: 3.279-28.6×10 -5 mm 3 N -1 m -1 .

[0046] Example 2

[0047] Step 1: Dissolve 50% of MoO3 and Bi2O3 in 50% of deionized water by mass percentage, mix thoroughly by mechanical ball milling, and dry. The mass ratio of MoO3 to Bi2O3 is 3:2, and the drying temperature is 70°C.

[0048] Step 2: According to the mass percentage, 25% of the first composite powder and 75% of the NiAl powder are placed in a three-dimensional mixer and mixed for 7 hours, and then placed in an oven at 80° C. for drying to obtain a second composite powder.

[0049] Step 3: On the substrate, NiAl phase is deposited on Inconel718 high temperature alloy by plasma spraying technology. A transition layer is formed on the substrate, and the thickness of the transition layer is 45 μm.

[0050] Step 4: Spray the second composite powder onto the transition layer by plasma spraying technology to form a surface layer comprising a NiAl transition phase and an oxide ceramic phase. The thickness of the surface layer is 190 μm, thereby obtaining a bimetallic oxide lubricating composite coating.

[0051] The performance of the obtained bimetallic oxide lubricating composite coating was tested: the surface hardness of the coating was 185.4±15.9Hv0.5, the bonding strength was 49.8±5.5Mpa, and the Figure 1 The cross-sectional morphology and element distribution of the composite coating show that the cross-sectional morphology of the coating presents a typical layered structure with a small amount of cracks, and the oxides are evenly distributed between the layers of the layered structure of the coating, which is beneficial to the continuous and uniform lubrication of the coating during the friction process.

[0052] High temperature friction test (27-800℃, ball-on-disk contact, dual ball material zirconia, rotation radius 5mm, speed 200r / min, load 10N): combined Figure 2 It can be seen that the friction coefficient of the composite coating changes in the range of 27 to 800°C. As the experimental temperature rises to 400°C, the friction coefficient of the composite coating decreases gradually, which means that when the temperature exceeds 400°C, a lubricating glaze film gradually forms on the wear surface, and the composite coating gradually softens. This is mainly because the melting points of MoO3 and Bi2O3 are 795°C and 825°C respectively, and they will undergo a brittle-ductile transition at 0.4 to 0.7Tm (about 320 to 560°C). Figure 3 It can be seen that the wear rate reaches the lowest value of 2.1×10 at 600℃. -5 mm 3 N -1 m -1 The main reason for this phenomenon is that the composite coating is prone to adhere to the dual surface during the friction process from room temperature to 200°C, due to the relatively soft metal oxide Bi2O3, which leads to an increase in the wear rate. Figure 4 As shown in Figure 2, when the temperature reaches 400°C, NiMoO4 and Bi2Mo3O 12 The lubricating glaze film composed of MoO3 and Bi2MoO6 reduces the wear rate of the coating, while no ternary oxide is generated inside the wear scar. At 800℃, although the friction surface has a lubricating glaze film, due to the low melting point MoO3 and Bi2O3 metal oxides, severe plastic deformation occurs, causing the wear rate to increase again. However, the friction coefficient and wear rate are relatively low between 400 and 600℃, indicating that the friction and wear performance of the NiAl-MoO3 / Bi2O3 composite coating is good at medium and low temperatures.

[0053] Example 3

[0054] Step 1: Dissolve 60% of MoO3 and Bi2O3 in 40% of deionized water by mass percentage, mix thoroughly by mechanical ball milling, and dry, wherein the mass ratio of MoO3 to Bi2O3 is 2:1, and the drying temperature is 80°C.

[0055] Step 2: 30% of the first composite powder and 70% of the NiAl powder, by mass percentage, are placed in a three-dimensional mixer and mixed for 10 hours, and then placed in a 90° C. oven for drying to obtain a second composite powder.

[0056] Step 3: On the substrate, NiAl phase is deposited on Inconel718 high temperature alloy by plasma spraying technology. A transition layer is formed on the substrate, and the thickness of the transition layer is 50 μm.

[0057] Step 4: Spray the second composite powder onto the transition layer by plasma spraying technology to form a surface layer comprising a NiAl transition phase and an oxide ceramic phase. The thickness of the surface layer is 180 μm, thereby obtaining a bimetallic oxide lubricating composite coating.

[0058] The performance of the obtained bimetallic oxide lubricating composite coating was tested: the surface hardness of the coating was 200.5±21.2Hv0.5, the bonding strength was 52.3±6.4Mpa, and the high temperature friction test (27-800℃, ball-disc contact, dual ball material zirconia, rotation radius 5mm, rotation speed 200r / min, load 10N): friction coefficient 0.18-0.65, wear rate: 4.919-20.9388×10 -5 mm 3 N -1 m -1 .

[0059] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a bimetallic oxide lubricating composite coating, characterized in that: A bimetallic oxide lubricating composite coating comprises a substrate, a transition layer covering the substrate and a surface layer covering the transition layer, wherein the transition layer is a NiAl phase, the surface layer comprises a NiAl phase and an oxide ceramic phase, and the oxide ceramic phase comprises MoO3 and Bi2O3; In terms of mass percentage, in the surface layer, the NiAl transition phase accounts for 70wt% to 80wt%, and the oxide ceramic phase accounts for 20wt% to 30wt%; The thickness of the transition layer is 40 μm to 50 μm, and the thickness of the surface layer is 180 μm to 200 μm; The mass ratio of the MoO3 to the Bi2O3 is (1-2):1; The substrate is a nickel-based high-temperature alloy; A method for preparing a bimetallic oxide lubricating composite coating comprises: Dissolve MoO3 and Bi2O3 in deionized water, mix well, and dry at 60-80° C. to obtain a first composite powder; when dissolving MoO3 and Bi2O3 in deionized water, the MoO3 and Bi2O3 account for 30%-60% by mass, and the deionized water accounts for 40%-70% by mass; The first composite powder and the NiAl powder are mixed evenly to obtain a second composite powder; when the first composite powder and the NiAl powder are mixed, the first composite powder accounts for 20% to 30% by mass, and the NiAl powder accounts for 70% to 80% by mass; On the substrate, the NiAl phase is sprayed by plasma spraying technology to form a transition layer; The second composite powder is sprayed on the transition layer by plasma spraying technology to form a surface layer including a NiAl transition phase and an oxide ceramic phase, that is, a bimetallic oxide lubricating composite coating is obtained.